1989
DOI: 10.1002/j.1460-2075.1989.tb08466.x
|View full text |Cite
|
Sign up to set email alerts
|

Reverse gyrase binding to DNA alters the double helix structure and produces single-strand cleavage in the absence of ATP.

Abstract: Stoichiometric amounts of pure reverse gyrase, a type I topoisomerase from the archaebacterium Sulfolobus acidocaldarius were incubated at 75°C with circular DNA containing a single-chain scission. After covalent closure by a thermophilic ligase and removal of bound protein molecules, negatively supercoiled DNA was produced. This finding, obtained in the absence of ATP, contrasts with the ATP-dependent positive supercoiling catalyzed by reverse gyrase and is interpreted as the result of enzyme binding to DNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 21 publications
5
48
0
Order By: Relevance
“…Together with previous studies using plasmids (7,9,20), these experiments with oligonucleotides further support the idea that the temperature dependence of the positive supercoiling reaction reflects the need for reverse gyrase to bind to locally denatured regions of the substrate.…”
Section: Dna Binding Behavior-supporting
confidence: 79%
See 3 more Smart Citations
“…Together with previous studies using plasmids (7,9,20), these experiments with oligonucleotides further support the idea that the temperature dependence of the positive supercoiling reaction reflects the need for reverse gyrase to bind to locally denatured regions of the substrate.…”
Section: Dna Binding Behavior-supporting
confidence: 79%
“…1), similar to the S. acidocaldarius and Desulfurococcus amylolyticus enzymes (10,18,19). Numerous studies indicate that this temperature dependence reflects the need for singlestranded regions in the plasmid substrate (7,9,20). At elevated temperature, the DNA strands of a duplex tend to separate locally, especially when the DNA is negatively supercoiled, and this allows reverse gyrase to gain access to the DNA.…”
Section: Overexpression and Properties Of Recombinant Reversementioning
confidence: 82%
See 2 more Smart Citations
“…The first reverse gyrase characterized was isolated from the hyperthermophilic archaeum Sulfolobus acidocaldarius (23,33). Mechanistic studies showed that it is transiently linked to the DNA by a 5Ј phosphotyrosyl bond (22,24), classifying it in the type I 5Ј topoisomerase family as proposed by Roca (38). Sequence analysis further showed that it is a single polypeptide containing putative helicase and topoisomerase domains located in the amino-and carboxy-terminal, respectively, parts of the protein (9).…”
mentioning
confidence: 99%